Dialectical Phenomenolgy : Marx's Method. - Bologh, Roslyn (Routledge revivals., 2009)
In this inquiry into Marx's method of theorising, originally published in 1979,€Roslyn Bologh analyses theory in the same way that Marx analyses the production of capital, and provides a set of rules for reproducing Marx's method. The rules are developed through an examination of the Grundrisse, €a text by Marx that combines his technical critique of political economy with his humanistic, philosophical concerns and his historical perspective. Dr Bologh concludes that Marx's method, as dialectical phenomenology, offers a way of analysing language, knowledge and the social relations an.